2010
DOI: 10.3945/ajcn.2009.28603
|View full text |Cite
|
Sign up to set email alerts
|

Feeding preterm infants milk with a higher dose of docosahexaenoic acid than that used in current practice does not influence language or behavior in early childhood: a follow-up study of a randomized controlled trial

Abstract: Feeding preterm infants milk containing 3 times the standard amount of DHA did not result in any clinically meaningful change to language development or behavior when assessed in early childhood. Whether longer-term effects of dietary DHA supplementation can be detected remains to be assessed. This trial was registered with the Australia and New Zealand Clinical Trial Registry at www.anzctr.org.au as 12606000327583.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 25 publications
2
56
0
1
Order By: Relevance
“…RBC-AA at 1 month of age was also found to be negatively associated with BSID-III receptive language and fine motor abilities at 1 year corrected age, but no associations were observed for DHA. The lack of a significant associations between breast-milk or RBC-DHA and developmental outcome are in line with previous observations [40][41][42], although some studies have demonstrated beneficial effects of DHA on psychomotor development in both term and preterm infants [35,[43][44][45]. A recent Swedish study found significant correlations between breast-milk AA and developmental outcomes at 40 weeks gestational age in preterm infants (born in gestational week 24-36) using the Brazelton Neonatal Behavioral Assesment Scale, which is very similar to the NNNS [16].…”
Section: Discussionsupporting
confidence: 80%
“…RBC-AA at 1 month of age was also found to be negatively associated with BSID-III receptive language and fine motor abilities at 1 year corrected age, but no associations were observed for DHA. The lack of a significant associations between breast-milk or RBC-DHA and developmental outcome are in line with previous observations [40][41][42], although some studies have demonstrated beneficial effects of DHA on psychomotor development in both term and preterm infants [35,[43][44][45]. A recent Swedish study found significant correlations between breast-milk AA and developmental outcomes at 40 weeks gestational age in preterm infants (born in gestational week 24-36) using the Brazelton Neonatal Behavioral Assesment Scale, which is very similar to the NNNS [16].…”
Section: Discussionsupporting
confidence: 80%
“…Two of the 3 studies that reported outcomes on child neurodevelopment showed no beneficial effects of LC-PUFA supplementation in preterm infants on cognitive outcomes at an early age [18 months; school age (language)] or behavior at 3 or 5 years of age (general cognitive tests at 10 years of age) [115,121,122]. However, beneficial effects of supplementation were observed in certain subgroups.…”
Section: Resultsmentioning
confidence: 99%
“…A review of randomized clinical trials (RCT) found that mental development for preterm infants fed LCPUFA-supplemented formula was significantly greater compared to control groups 6 . Moreover, there was no clinically significant effect of high-DHA supplemented formula on language, behavior, and temperament using the MacArthur Communicative Development Inventory 7 or between maternal DHA supplementation and neurodevelopmental scores assessed by the Bayley-III 8 . Differences in the results may be related to the use of global, rather than specific areas of cognition tests or a gender effect in which only girls were found to have positive response to LCPUFA supplementation 9 .…”
Section: Introductionmentioning
confidence: 89%
“…Breast milk was not associated with expressive language (Bayley-II), but maternal education was associated, and no differences were found between formula-and breast-fed term infants on tests of receptive vocabulary (Peabody Picture Vocabulary TestRevised) and expressive vocabulary (mean length of utterance) 28 . Moreover, no evidence of improved language development was observed between infants fed 1% DHA versus 0.3% DHA breast milk using the MacArthur Communicative Development Inventory (MCDI) 7 . Confounding factors such as socioeconomic status and maternal education need to be taken into consideration.…”
Section: Commentmentioning
confidence: 99%